Problems of Diagnosis, Conservative Treatment and Long-Term Results of “Mallet Finger” Fracture - Bezuhlyi, A.A.; Lysak, A.S. (TERRA ORTHOPAEDICA, 2021)
Summary. Distal phalanx dorsal edge fracture is treated in a relatively simple closed manner during the first weeks after injury. The role of the distal interphalangeal joint in the upper extremity integral function reaches conventionally only a few percent. This may lead to insufficient attention and a large number of mistakes in diagnosis and treatment of such injuries, which in turn provokes complications that are much more difficult to treat than the primary injury. This article considers the most common problems of diagnosis and treatment of “mallet finger” fractures. Advantages and disadvantages of various techniques used in the treatment of such fractures in acute and neglected cases are considered and analyzed. Objective: to study the effect of distal phalanx dorsal edge avulsive fractures on function of the upper limb, quality of life, and depression rate in long term period after injury. Materials and Methods. Data from 11 patients (8 (88%) males and 3 (12%) females) with neglected cases of distal phalanx dorsal edge avulsive fractures were studied. QuickDASH questionnaire and visual analog scales were used to study impaired quality of life and depression rate in such patients. Indicators that lead to the need for surgery in long term period after injury have been identified. Results. It was determined that in long term period, in patients with a “mallet finger” fracture, function of the upper extremity suffered significantly and was 29.2±20.2 points (range 2.3-75) according to QuickDASH scale. This condition also significantly affected the general well-being of the patient. Average value of impaired quality of life was 43.6±24.6 (range 0-90 points), and depression rate due to upper extremity dysfunction was 44.6±22.7 (range 0-90 points). Conclusions. Despite the relatively minor injury, high rates of dysfunction, impact on quality of life and depression rate indicate the need to restore finger function even in long term period after injury.